Impact of Culture and Traditional Dietary Habits on Gastric Cancer Carcinogenesis in East Asia - Liu, Kylie; Wu, PhD*, Yongzhong (North American Journal of Medicine and Science, 2025)
Gastric cancer is one of the most common and deadly malignant neoplasms. Its incidence significantly varies by region. Most cases of newly diagnosed gastric cancer were reported in East Asian countries where there are unique cultures and traditional dietary habits. Culture affects eating habits and influences dietary choices. People in East Asia traditionally have high salt consumption rates and eat many salt-preserved foods/pickled foods, which have been well described as important risk factors in the carcinogenesis of gastric cancer. High dietary salt intake directly damages gastric tissue, facilitates colonization by Helicobacter pylori (H. pylori) infection, and amplifies the activity of bacterial virulence factors such as CagA, thereby accelerating carcinogenesis. In East Asian countries, the incidence of H. pylori infection is significantly higher. Studies demonstrated that dietary habits correlated significantly with H. pylori infection. Recent molecular evidence suggests that H. pylori plays a significant role in the initiation and development of gastric cancer. The roles of miRNA dysregulation and signaling pathway alterations has also played a role in the carcinogenesis of gastric cancer. The interplay of diet, culture, and microbial infection underscores the importance of modifiable risk factors in shaping gastric caner outcomes. Recognizing these patterns provides a foundation for prevention strategies and public health policies tailored to the particularly high-risk populations of East Asia. [N A J Med Sci. 2025;18(1):032-037. DOI: 10.7156/najms.2025.1801032] Key Words: Culture, Tradition, Dietary habit, East Asia, Gastric cancer